The effectiveness of police forces through centuries: The evolution of training process in contemporary social context - Milojević Saša; Milojković Boban; Janković Bojan (NBP: Nauka, bezbednost, policija)
By researching the emergence and development of police training, it is considered how, throughout history, the structure and organization of police forces were shaped, with special emphasis on the processes of education, permanent training and professional development. The evolution of police training in response to dynamic social change and growing demands for professionalism, specialization and certification are being considered. Approaches to training in different countries are analysed, showing how national and international factors shape educational methods and goals. The paper also sheds light on how theoretical knowledge and practical skills in training contribute to the effectiveness and efficiency of police work in modern society. The paper aims to provide insight into key trends and challenges in police training, with the perspective of further improvement and adaptation of educational strategies to respond to the demands of the modern age.